Modeling Digital Image Segmentation with Canny Method - Ptr, Agus Fahmi Limas; Rosnelly, Rika; Junaidi, Junaidi; Amrullah, Amrullah (Sinkron : jurnal dan penelitian teknik informatika, 2023)
In general, the segmentation process is divided into three parts. classification, by edge, and by area. The digital image segmentation process divides an object whose surface or background maintains the RGB value of all pixels of a digital image so that the object can be processed for other purposes. This system aims to execute drawing objects using intelligent methods. In the Canny method, the process begins with taking digital images and continues with the grayscale process. In addition, technique selection starts with performing a complex operator or Laplacian edge detection and finally unlocks it. Successful segmentation results using edge detection with intelligent operators to separate objects. This system uses the Matlab 2017 application.